Defunding the police through shared service agreements: the impact on cost savings, staffing, and public safety using a bias-corrected synthetic control analysis - Mazeika, David (Criminology & public policy, 2023)
New Jersey (NJ) is home to more than 460 municipal police departments, including close to 60 with fewer than 11 officers. In total, the state spends around $3 billion per year on policing, 20% of the typical municipal budget. In recent history, seven NJ municipalities have disbanded their local force and contracted services with a neighbor. Using the bias-corrected synthetic control method, results from this study reveal these locations saved on average $143 per person per year, close to 300,000 Dollar per municipality. There were fewer officers in the contracting force per capita postcontracting, but no effects on public safety. Contracting agencies also gained new services including a K-9 Unit and full-time detectives. However, the monies municipalities saved were largely used to cut taxes and fund capital improvements, not to fund reform efforts called for after the murder of George Floyd. Contracting thus was a way to maintain the status quo.